THE EFFECTS OF A SOCIAL-EMOTIONAL LEARNING (SEL) CURRICULUM ON ACADEMIC RESILIENCE AND PROSOCIAL BEHAVIOR IN HIGH-POVERTY PRIMARY SCHOOLS AT SDN NO.100907 MUARA AMPOLU I KECAMATAN MUARA BATANGTORU - Hendri Junaidi Nasution; Sery Bulan Harahap; Luthfi Azima Harahap; Anita Adinda; Hamka (PT. Jurnal Center Indonesia Publisher, 2025)
This study examines the effects of a Social-Emotional Learning (SEL) curriculum on academic resilience and prosocial behavior in high-poverty primary schools, specifically at SDN No. 100907 Muara Ampolu I, Kec. Muara Batangtoru. Employing a quasi-experimental design with a pretest-posttest control group, 80 students participated, divided equally into intervention and control groups. The 12-week SEL program focused on self-awareness, self-management, social awareness, relationship skills, and responsible decision-making. Data were collected using validated academic resilience and prosocial behavior instruments and analyzed through paired and independent sample t-tests. Findings revealed that students in the intervention group demonstrated significant improvements in academic resilience and prosocial behavior compared to the control group. The study highlights the potential of SEL curricula to foster adaptive coping strategies and positive social interactions among students in socioeconomically disadvantaged settings. Implications for educational policy and school practices are discussed, emphasizing the importance of SEL integration in primary education